2020
DOI: 10.1002/1438-390x.12043
|View full text |Cite
|
Sign up to set email alerts
|

Population responses of roe deer to the recolonization of the French Vercors by wolves

Abstract: In a context of changing carnivore populations worldwide, it is crucial to understand the consequences of these changes for prey populations. The recolonization by wolves of the French Vercors mountain range and the long‐term monitoring (2001–2017) of roe deer in this area provided a unique opportunity to assess the effects of wolves on this prey. Roe deer was the main prey of wolves in the west Vercors mountain range during this recolonization. We compared roe deer abundance and fawn body mass in two contrast… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 75 publications
(93 reference statements)
0
5
0
1
Order By: Relevance
“…9, 18, 19, and 22 and SI Appendix), because abundant evidence indicates such impacts may be almost universal in birds and mammals (1,22). Parental care is a fundamental characteristic of most birds and all mammals (34), fear has been shown to impair parental investment and care in diverse birds and mammals (1,(35)(36)(37)(38)(39)(40)(41), reduced care consistently results in poorer offspring condition and consequent lower survival (15,30), and there is correspondingly a growing body of experimental and observational research documenting resulting reductions in fecundity and offspring survival in free-living birds and mammals, comparable to those demonstrated in our experiment (1,16,17,20,21,42,43). Numerous studies have shown that one of the principal and almost universal costs prey incur in attempting to avoid being killed is reduced food intake due to increased vigilance or avoidance of predators (1-3, 6, 10, 11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9, 18, 19, and 22 and SI Appendix), because abundant evidence indicates such impacts may be almost universal in birds and mammals (1,22). Parental care is a fundamental characteristic of most birds and all mammals (34), fear has been shown to impair parental investment and care in diverse birds and mammals (1,(35)(36)(37)(38)(39)(40)(41), reduced care consistently results in poorer offspring condition and consequent lower survival (15,30), and there is correspondingly a growing body of experimental and observational research documenting resulting reductions in fecundity and offspring survival in free-living birds and mammals, comparable to those demonstrated in our experiment (1,16,17,20,21,42,43). Numerous studies have shown that one of the principal and almost universal costs prey incur in attempting to avoid being killed is reduced food intake due to increased vigilance or avoidance of predators (1-3, 6, 10, 11).…”
Section: Resultsmentioning
confidence: 99%
“…Progress has recently been made in experimentally demonstrating the community-level impacts fear of predators can have in wildlife systems (1), which has drawn attention to the contrasting "dearth (absence) of evidence" concerning the impact on population growth (1,10,11). Critically, this dearth does not concern the various components, such as fear effects on parental care, fecundity, or offspring survival, for which there is an abundance of evidence (1,9,(35)(36)(37)(38)(39)(40)(41), but rather the absence of demonstrations that these components do all link together to affect prey population growth (1,10,11). The significance of our eliminating this absence by experimentally demonstrating that these components can all link together and that fear itself can impact prey population growth rates in free-living wildlife is that it verifies that, from the commonality of the components, fear effects on prey population growth rates, while not necessarily universal, can be anticipated to be commonplace (1-3, 6, 8-11).…”
Section: Discussionmentioning
confidence: 99%
“…Whether large predators may impede the spread and growth of muntjac populations remains to be seen. The grey wolf (Canis lupus) has been growing and spreading across much of Europe in recent years (Herzog 2018) and can regulate roe deer (Capreolus capreolus) populations (Randon et al 2020). Improved understanding of the responses of wolves to the increasing presence of muntjac and the response of muntjac populations to wolf presence and predation could offer insight into the nature of predator-mediated trophic cascades (Letnic and Ripple 2017) when impacted by an invading nonnative species, and the potential role of native predatory mammals in regulating (or not regulating) invasive non-native mammals (see Sheehy and Lawton 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In the French Alps, roe deer fawn body mass was consistently lower in wolf core areas compared to peripheral areas (Randon et al, 2020). The mechanisms of such a difference in body mass in response to wolf presence are unclear.…”
Section: Physiological Effects and Parasite Prevalencementioning
confidence: 98%